Influence of Saccharomyces boulardii CNCM I-745on the gut-associated immune system - Stier, Heike (Clin Exp Gastroenterol, 2016)
BACKGROUND: The probiotic Saccharomyces boulardii CNCM I-745 (also known as Saccharomyces cerevisiae HANSEN CBS 5926; in the following S. boulardii) has proven its effectiveness in preventive and therapeutic treatment of many gastrointestinal diseases, especially diseases associated with acute diarrhea. In particular, antibiotic-associated diarrhea, Clostridium difficile-associated diarrhea, traveller’s diarrhea, as well as acute diarrhea due to common viral and bacterial infections in children and adults. AIM: The aim of this review is to summarize the experimental studies elucidating the molecular and immunological mechanisms by which these clinically proven effects are archived, with an emphasis on the gut-associated immune system. The main focus is laid on anti-inflammatory and immune-modulatory action of S. boulardii involved in bacterial or enterotoxin-mediated diarrhea and inflammation. An attempt is made to differentiate between the effects associated with cellular versus soluble factors and between prophylactic and therapeutic effects. METHODS: A literature search was performed in PubMed/PubMed Central for the effects of S. boulardii on the gut-associated immune system (focus acute diarrhea). RESULTS AND CONCLUSION: S. boulardii exhibits its positive effect by the direct effects on pathogens or their toxins as well as by influencing the host’s infection-induced signaling cascades and its innate and adaptive immune system. The combination of these mechanisms results in a reduction of the pathogens’ ability for adhesion or colonization and an attenuation of the overreacting inflammatory immune response. Thereby, the integrity of the intestinal epithelial cell layer is preserved or restored, and the diarrheic leakage of fluids into the intestinal lumen is attenuated.